The Role of Engagement and Convergence in the Retention of Elites in Afghanistan (Salam International Academic Journal, 2025)
The retention of elites in Afghanistan represents one of the key challenges to achieving sustainable development and realizing social, economic, and political progress. As essential components of human capital, elites play a critical role in driving national transformation. However, a range of factors—such as corruption, social inequalities, political instability, and the lack of suitable employment opportunities—have contributed to increased emigration and weakened engagement between elites and society.This study employs a descriptive-analytical and inductive methodology to examine the role of engagement and convergence in fostering the long-term presence of elites in Afghanistan. It also assesses the key determinants of their retention. The findings indicate that enhancing transparency and accountability in governance, strengthening the educational system, ensuring social justice, expanding employment opportunities, improving security and political stability, and supporting professionals are among the most effective strategies for retaining elites within the country.Achieving this objective, and thereby advancing sustainable development in Afghanistan, requires comprehensive collaboration between the state and its elite class to establish a conducive environment for growth and progress.
Keywords: Elites; Engagement; Convergence; Social Justice; Educational System; Political Stability